Through rose-tinted glasses: How inducing and resolving curiosity makes consumers less skeptical and improves their product evaluations - Verena Hüttl-Maack; Tara M. Sedghi; Jana M. Daume (Journal of Consumer Psychology, 2023)
Research indicates that in general, curiosity leads to more intense processing of an advertisement, which might result in a more skeptical response toward a persuasive message. However, we propose the opposite and argue that a process of evoking curiosity toward a stimulus in the first step (with the creation of an information gap) and resolving it in the second step creates a positive affective experience. Upon receiving curiosity-resolving information after becoming curious, consumers are less skeptical toward the advertised product, which leads to a more favorable attitude and a higher purchase intention. Based on four studies, we demonstrate curiosity's skepticism-reducing effect, its downstream consequences, and the underlying mechanism of positive affect. We show that this curiosity-stimulating way of information disclosure caused the effect instead of the information itself, which remained constant. The effects occur for integral curiosity, directed at the focal product, and for incidental curiosity, elicited by an unrelated stimulus. These results contribute to understanding consumer responses to curiosity-evoking advertisements, which are widespread, and provide implications for consumer psychologists, practitioners, and policy makers.
Keywords: 650; advertising; consumer skepticism; curiosity; persuasion; positive affect